2018
DOI: 10.1038/s42003-018-0152-1
|View full text |Cite
|
Sign up to set email alerts
|

Bone morphogenetic protein signaling is required for RAD51-mediated maintenance of genome integrity in vascular endothelial cells

Abstract: The integrity of blood vessels is fundamental to vascular homeostasis. Inactivating mutations in the bone morphogenetic protein (BMP) receptor type II (BMPR2) gene cause hereditary vascular disorders, including pulmonary arterial hypertension and hereditary hemorrhagic telangiectasia, suggesting that BMPR2 and its downstream signaling pathway are pivotal to the maintenance of vascular integrity through an unknown molecular mechanism. Here we report that inactivation of BMPR2 in pulmonary vascular endothelial c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 75 publications
(119 reference statements)
1
17
1
Order By: Relevance
“…The results also validated with small interfering RNA (siRNA) revealed enhanced expression of CHK-1 upregulates RAD-51 [ 73 ]. This contrasts with the findings in PAECs in a separate study, where BMPR2-deficient PAECs showed a reduced level of RAD51 and lung tissue from IPAH patients had attenuated RAD51 levels [ 77 ]. In vivo studies supported the therapeutic potential of the CHK-1 inhibitor by reducing the hemodynamic parameters associated with increased DNA damage in fawn-hooded rats with already developed PAH; however, no reduction in RV hypertrophy was observed [ 73 ].…”
Section: Dna Repair Pathways and Cell Cycle Checkpoints In Pahcontrasting
confidence: 89%
See 4 more Smart Citations
“…The results also validated with small interfering RNA (siRNA) revealed enhanced expression of CHK-1 upregulates RAD-51 [ 73 ]. This contrasts with the findings in PAECs in a separate study, where BMPR2-deficient PAECs showed a reduced level of RAD51 and lung tissue from IPAH patients had attenuated RAD51 levels [ 77 ]. In vivo studies supported the therapeutic potential of the CHK-1 inhibitor by reducing the hemodynamic parameters associated with increased DNA damage in fawn-hooded rats with already developed PAH; however, no reduction in RV hypertrophy was observed [ 73 ].…”
Section: Dna Repair Pathways and Cell Cycle Checkpoints In Pahcontrasting
confidence: 89%
“…Consistent with the downregulation of BMPR2 under a DNA-damaging environment, Vattulainen-Collanus and colleagues uncovered a previously unknown role of BMP signaling in the protection of cells from genomic insult [ 77 ]. They showed that MMC treatment reduced the expression of BMPR2, BRCA1, and RAD51.…”
Section: Bmpr2 and Dna Damagementioning
confidence: 88%
See 3 more Smart Citations